Development of Canva-Based Online Comic Learning Media on the Material of the Proclamation of Independence of the Republic of Indonesia - Putra Pratama; Wayan Satria Jaya; Ozi Hendratama (CV Projurnal Mitra Publikasi, 2025)
This research is motivated by several factors, including teacher-centered learning, which makes students less active and often passive. Educators have not yet utilized diverse learning media to engage students effectively. Additionally, students show low enthusiasm for participating in lessons and have limited interest in reading. The teaching and learning process is further constrained by limited material due to inadequate use of time, media, and infrastructure. Lastly, the potential of comic-based learning media remains underdeveloped. The aim of this research is to determine the need for Canva-based online comic learning media during the proclamation of independence of the Republic of Indonesia for students in class XI TKJB SMK Nurul Islam. The research model used is the ADDIE research and development model (Analysis, Design, Development, Implementation, Evaluation. The subjects of this research were 34 students of class XI TKJB SMK Nurul Islam. Based on the responses of educators and students to the development of Canva-based online comics based on material from the event of the proclamation of independence of the Republic of Indonesia. Based on user responses during small group trials consisting of 4 students, the average rating percentage was 83%, including in the